ORMATION OF FINANCIAL SUPERMARKETS AS COMPETITIVENESS OF BANKS ON THE FINANCIAL MARKET - Dmitry Maksimov; Vyacheslav Monin; Julia Konopleva (Вестник Северо-Кавказского федерального университета, 2022)
In this article, the financial supermarket is considered as a fight against the problem of reducing the proitability of speciic business areas. The distinctive features of banks, the following strategies of the financial supermarket, as well as the goal of creating financial supermarkets on the market are determined. Pros and cons of financial supermarkets. Application of the business model of a financial supermarket in the Russian Federation. Consideration of JSC «Tinkoff Bank», as an example, seeking to become a financial supermarket on the market.